Modulating N-H-Based Excited-State Intramolecular Proton Transfer by Different Electron-Donating/Withdrawing Substituents in 2-(2’-Aminophenyl)Benzothiazole Compounds (Journal of Atomic and Molecular Sciences, 2018)
At the B3LYP/6-311+G(d, p)/IEFPCM (in dichloromethane) theory level, the N-H-based excited-state intramolecular proton transfer (N-H-based ESIPT) process of 2-(2’-aminophenyl)benzothiazole (PBT-NH2) and its three derivatives 2-(2’-methylaminophenyl) benzothiazole(PBT-NHMe), 2-(2’-acetylaminophenyl)benzothiazole (PBT-NHAc) and 2-(2’-tosylaminophenyl) benzothiazole (PBT-NHTs) have been explored by the time-dependent density functional theory (TD-DFT) method. Our calculated hydrogen bond lengths and angles sufficiently confirm that the intramolecular hydrogen bonds $N_1-H$•••$N_2$ formed at the $S_0$ states of the four compounds should be significantly strengthened in the $S_1$ state, which are further supported by the results obtained based on the analyses of infrared spectra shifts. The scanned potential energy curves reveal that the energy barriers of the first singlet excited state of the four titled compounds along the ESIPT reactions are predicted at 8.74, 8.98, 6.72 and 1.69 kcal/mol, respectively, suggesting that the inclusion of a strong electron-withdrawing tosyl (Ts) group can remarkably facilitate the occurrence of the ESIPT reaction, while the involvement of an electron-donating methyl group has slight opposite effect on the ESIPT process of the amino-type hydrogen-bonding system.